Satisfaction across urban consumers of smallholder-produced teak (Tectona grandis L.f.) poles in South Benin - AOUDJI, KOSSI NOUNAGNON AUGUSTIN; ADEGBIDI, ANSELME BIENVENU E. ADÉNIYI; GANGLO, COSSI JEAN; AGBO, AKPADJI VALENTIN; YEVIDE, Armand S. I.; De CANNIERE, Charles; Lebailly, Philippe (My University, 2011)
The study used the expectancy-disconfirmation framework to investigate the satisfaction among urban consumers of teak pole in South Benin, so as to identify the areas where interventions are needed to secure market opportunity for smallholder forestry. A survey was conducted in five cities; and 223 household-heads were interviewed using systematic sampling, with a random start. Data were collected on socio-demographic characteristics, teak pole consumption forms, behaviour patterns, and motivations. Respondents also rated their expectations and perceptions for a set of nine attributes on a 7 points Likert scale. Hierarchical ascending cluster analysis was performed to identify consumer segments; and satisfaction level was analysed per segment, by determining the gap between expectations and perceptions, for all attributes. Four consumer segments were identified; and socio-demographic profiles differed across those segments. Competitive price was an important purchasing motivation across the identified segments. Consumers were dissatisfied with price, availability, knot frequency, bending, length, hardness, and durability of teak pole. The efforts to meet the consumer expectations should be concentrated on building farmers’ capacity in silvicultural management, and ensuring the availability of good planting material. The issue of competitive price might be addressed, through the improvement of the overall efficiency in the value chain.
Keywords: consumer; satisfaction; profile; smallholder forestry; teak; pole; marketing.